1990
DOI: 10.1111/j.1464-410x.1990.tb14688.x
|View full text |Cite
|
Sign up to set email alerts
|

Voiding Patterns in Men Evaluated by a Questionnaire Survey

Abstract: A questionnaire on obstructive and irritative voiding symptoms was sent to 572 men aged between 20 and 79 years, selected at random from the National Register; 337 questionnaires were completed. None of the responders had consulted a doctor because of voiding symptoms. There was a significant increase in voiding symptoms and in the obstructive, irritative and total symptom scores between the sixth and seventh [corrected] decades, whereas the increases in the other decades were small. Only the prevalence of ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0

Year Published

1990
1990
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(36 citation statements)
references
References 17 publications
3
33
0
Order By: Relevance
“…This systematic review identified a total of 31 studies 6, 1039 with sufficiently suitable data (Fig. 1) obtained from 25 countries.…”
Section: Resultsmentioning
confidence: 99%
“…This systematic review identified a total of 31 studies 6, 1039 with sufficiently suitable data (Fig. 1) obtained from 25 countries.…”
Section: Resultsmentioning
confidence: 99%
“…Sommer et al [13,14] found that the percentage number reporting three or more voiding episodes at night increased among both males and females from adolescence (0%) to the age of 60 -70 years (11%).…”
Section: Age-related Development Of Nocturiamentioning
confidence: 96%
“…Further studies of women aged 20-79 years showed that daytime urinary frequency remained unchanged with age (mean 6.1 voids). In contrast, nocturia increased significantly, with 23% of women in their 60s and 28% in their 70s needing to void at least twice during the night (36,37).…”
Section: Bladder Functionmentioning
confidence: 78%